Reliability enhancement of complex networks through redundancy scaling - Al-Khateeb, Wajdi Fawzi Mohammed; Al-Irhayim, Sufyan; Al-Khateeb, Khalid A. Saeed (2010)
The conventional Internet backbone exhibits significant less reliability than the Public Switched Telephone Network. MPLS based Internet core network adopts principles of reliability implemented in the circuit-switched telecom networks characterized by high reliability/availability figures of 99.99% and 99.999%. Such core network is modeled by an n-tuple bridge complex network. In order to enhance the reliability of this structure to figures required by QoS application, two types of recurrent redundancies are considered in this paper. The first approach implements external multiple backup paths that transform the n-tuple bridge into an mxn matrix network. The second one uses internal embedded recurrent redundancy the substitute each of the links in the n-tuple bridge by a bridge network. The reliability enhancement of the two schemes is analyzed, with regard to the number of backups in case of the mxn matrix network and in term of the recurrence of the embedding in case of the n-tuple bridge. Finally, the reliability enhancement of both schemes is compared with respect to each other.